Psychometric study of the university’s learning motivation scale - Santos, Acácia Aparecida Angeli dos (2013)
This study objective was to search evidence of validity by items internal structure analysis to the University’s Learning Motivation Scale, as well as to investigate the internal consistency and differences between gender, age and area of expertise. The participants consisted of 429 students from a private university in São Paulo, with ages ranging from 18 to 44. The instrument used was the University’s Learning Motivation Scale. The results showed that the scale items got into three factors, which are performance-avoidance goal, performance-approach goal and learning goal. These factors, explained 39.41% of the scale variance. The three factors’ internal consistency ranged from 0.72 to 0.83. Comparing goals in relation to gender the findings showed a significant difference in performance-approach goal. Related to age there was differences found in learning goal. These results showed that the levels of validity and reliability are acceptable, however, further studies are needed to increase knowledge about the scale psychometric characteristics.